2013
DOI: 10.1055/s-0032-1329179
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Oxytocin Receptor Expression at Term Is Related to Maternal Body Mass Index

Abstract: Oxytocin receptor, but not connexin-43, expression is related to BMI, suggesting an alteration in oxytocin receptor expression or function related to obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
(41 reference statements)
0
12
0
1
Order By: Relevance
“…The hormonal milieu of an obese woman appears to interact with oxytocin regulation and response, and/or affect myometrium contractility. It is possible that increased BMI leads to variation in expression and function of the oxytocin receptor of the human myometrium [15], which explains the higher doses of oxytocin required in obese patients. Further, leptin, methyl palmitate, and apelin are overexpressed in obese women, and have all been shown to impact myometrium contractility [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hormonal milieu of an obese woman appears to interact with oxytocin regulation and response, and/or affect myometrium contractility. It is possible that increased BMI leads to variation in expression and function of the oxytocin receptor of the human myometrium [15], which explains the higher doses of oxytocin required in obese patients. Further, leptin, methyl palmitate, and apelin are overexpressed in obese women, and have all been shown to impact myometrium contractility [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that a complex interplay of hormonal modulators produced in adipose tissue could inhibit myometrial contractility [12][13][14]. In vitro studies also suggest that oxytocin receptor expression and/or function is affected by body mass index (BMI, calculated as weight in kilograms divided by the square of height in meters) and that oxytocin response is somehow blunted by obesity [15]. Indeed, treatment of protracted labor with oxytocin has been shown to be less effective in obese patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism remains unclear, the hormonal milieu of obese women, which appears to interact with oxytocin regulation and response, may affect myometrium contractility, as well as the variation in expression and function of the oxytocin receptor of the human myometrium caused by increased BMI. [ 17 ] This may explain in part why obese women may have a longer labor. Unfortunately, we did not have a sufficient number of very obese women for a stratified analysis for labor progression by BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggest that oxytocin receptor expression is affected by BMI, and oxytocin response is blunted by obesity. 57 Several studies have demonstrated that as BMI increases, oxytocin requirement increases. [50][51][52][53] In a retrospective study of singleton, term (≥37 weeks) pregnant patients who received augmentation after spontaneous labor (n = 413), obese patients trended toward more cumulative oxytocin (minimum: 24.7 ± 100.5 mU among patients with a BMI of 18.50-24.99 kg/m 2 ; maximum: 1580.5 ± 2530.5 mU among patients with a BMI of 35.00-39.99 kg/m 2 ; P = 0.09).…”
Section: Oxytocinmentioning
confidence: 99%
“…Another important consideration in oxytocin management is body mass index (BMI). In vitro studies suggest that oxytocin receptor expression is affected by BMI, and oxytocin response is blunted by obesity 57 . Several studies have demonstrated that as BMI increases, oxytocin requirement increases 50–53 .…”
Section: Augmentation Techniquesmentioning
confidence: 99%